Basic technical analysis of financial markets : a modern approach - Di Lorenzo, Renato (Perspectives in Business Culture,, 2013)
The present book avoids the fantasy recipes that abound in technical analysis and focuses instead on those that are statistically correct and can be understood by newcomers as well as appreciated by professionals. The described protocols and techniques will prove invaluable in analyzing market behavior and assisting in trading decisions. The algorithms used in the technical analysis of financial markets have changed beyond recognition. This book offers a more efficient technical analysis - one that is not satisfied with protocols that just seem to be fine, but which requires that they are indeed fine, verifying this through simulations on the PC, serious statistical counts, and so on.